690 CD122-selective IL-2 complexes treat ovarian carcinomas, induce Treg fragility and promote T cell stem cells. (9th November 2020) - Deng, Yilun; Drerup, Justin; Zhang, Xinyue; Reyes, Ryan; Mendez, Jenny; Kancharla, Aravind; Garcia, Myrna; Bai, Haiyan; Padron, Alvaro; Gupta, Harshita; Curiel, Tyler
Abstract : Background: Ovarian cancer (OC) responds poorly to immunotherapies. Regulatory T cells (Treg) engage IL-2 by high-affinity CD25 for differentiation and function, 1 and anti-tumor effector T cells (Teff) use intermediate affinity CD122. We studied IL-2 complexes (IL-2c) that selectively activate CD122 (Teff) over CD25 (Tregs). Methods: Orthotopic ID8agg-luc mouse OC burden was measured by in vivo imaging. Tumor, ascites and draining lymph nodes (TDLN) were analyzed by flow and tSNE. IL-2c was complexed using 1.5 µg/mouse IL-2 and 7.5 µg/mouse aIL-2 (clone JES6-5H4) before i.p. injection every other day x 4 starting at day 7. antiPD-L1 was given at 100ug/mouse every 3 days x 4 starting from Day 11. FIR mice 2 were used to sort live Tregs. Results: IL-2c but not antiPD-L1 potently inhibits ID8agg (figure 1). IL-2c decreased ascites Treg functional markers (e.g., CD25, granzymeB) while upregulating the same markers on Teffs (figure 2). IL-2c inhibited Treg suppression in ascites while TDLN Tregs were unaffected (figure 3). tSNE showed great similarity of TDLN Tregs treated with isotype and IL-2c while ascites Tregs after IL-2c showed a fragile phenotype (e.g., increased PD-1, T-bet, and IFNgamma with maintained FoxP3 expression [figure 4]) which is known to contribute to better response to cancer immunotherapy. 3 4 We observed a complete reduction of tumor bioluminescence with IL-2c and antiPD-L1 combo treatment in nearly all subjects significantly exceeding effect of IL-2c alone (figure 5). A CD8+CXCR5+TCF-1+ T cell stem cell (TCSC) population reportedly improves immune checkpoint blockade efficacy. 5 6 Since CD122 is regulated by TCF-1, 7 we explored the effect of IL-2c on these TCSC. IL-2c significantly induced a CD8+TCF-1+ TCSC population in ID8agg tumors (figure 6), possibly through a positive feedback loop by further enhancing CD122 expression on TCF-1+, but not TCF-1- cells (figure 7). tSNE analysis of detailed immune phenotype of IL-2c induced TCSC revealed that these TCSC differed from those induced by antiPD-L1. In ID8agg, antiPD-L1-induced TCSC are mostly CXCR5+ and PD1+, consistent with previous reports in other cancers 3 4 while IL-2c-induced TCSC were PD1- (figure 8), expressed CCR2 and CXCR3, and produced TNFalpha (figure 9). Conclusions: We define two novel IL-2c effects: inducing Treg fragility therefore reducing immunosuppression while promoting TCSC that could enhance effective anti-tumor immunity. Current work tests if effects are related and help efficacy, and mechanisms for IL-2c Treg effects. We also show that elicited TCSC differ by treatment and tumor, requiring additional investigations. Acknowledgements: This work is supported by CPRIT Research Training Award (RP 170345), Ovarian Cancer Research Alliance Ann and Sol Schreiber Mentored Investigator Award to YD and R01 CA205965to TC. Ethics Approval: All mice studies were approved by UT Health San Antonio Institutional Animal Care and Use Committee (IACUC). Approval number 20150093AR, 20140001AR, 20170035AR, 20140039AR, 20140027AR, 20090128AR, 20120071AR, 20180021AR. References: Malek TR: The biology of interleukin-2. Annu Rev Immunol 2008, 26:453–479. Fantini MC, Dominitzki S, Rizzo A, Neurath MF, Becker C: In vitro generation of CD4+ CD25+ regulatory cells from murine naive T cells. Nat Protoc 2007, 2(7):1789–1794. Overacre-Delgoffe AE, Chikina M, Dadey RE, Yano H, Brunazzi EA, Shayan G, Horne W, Moskovitz JM, Kolls JK, Sander C, et al: Interferon-gamma Drives Treg Fragility to Promote Anti-tumor Immunity. Cell 2017, 169(6):1130–1141e1111. Overacre-Delgoffe AE, Vignali DAA: Treg Fragility: A Prerequisite for Effective Antitumor Immunity? Cancer Immunol Res 2018, 6(8):882–887. Brummelman J, Mazza EMC, Alvisi G, Colombo FS, Grilli A, Mikulak J, Mavilio D, Alloisio M, Ferrari F, Lopci E, et al: High-dimensional single cell analysis identifies stem-like cytotoxic CD8(+) T cells infiltrating human tumors. J Exp Med 2018. Sade-Feldman M, Yizhak K, Bjorgaard SL, Ray JP, de Boer CG, Jenkins RW, Lieb DJ, Chen JH, Frederick DT, Barzily-Rokni M, et al: Defining T Cell States Associated with Response to Checkpoint Immunotherapy in Melanoma. Cell 2018, 175(4):998–1013 e1020. Jeevan-Raj B, Gehrig J, Charmoy M, Chennupati V, Grandclement C, Angelino P, Delorenzi M, Held W: The Transcription Factor Tcf1 Contributes to Normal NK Cell Development and Function by Limiting the Expression of Granzymes. Cell Rep 2017, 20(3):613–626.